2019
DOI: 10.1186/s12969-019-0333-6
|View full text |Cite
|
Sign up to set email alerts
|

Early administration of adalimumab for paediatric uveitis due to Behçet’s disease

Abstract: Background Behçet’s disease is a chronic inflammatory multisystem disorder that is characterised by oral and/or genital ulcerations as well as intraocular inflammation. Recurrent retinal vasoocclusive episodes and macular involvement may lead to severe loss of visual acuity. Patients may eventually become resistant to systemic corticosteroid and develop side effects; therefore, other immunosuppressive therapies are needed. Biologic agents are promising for the treatment of Behçet’s disease-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Thirty articles included for the final review are composed of two systematic reviews with metaanalysis [11,12], fifteen case reports/series [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and thirteen observational studies [1,3,4,9,[28][29][30][31][32][33][34][35][36][37]. The two systematic reviews provided data on 692 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty articles included for the final review are composed of two systematic reviews with metaanalysis [11,12], fifteen case reports/series [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and thirteen observational studies [1,3,4,9,[28][29][30][31][32][33][34][35][36][37]. The two systematic reviews provided data on 692 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The US Food and Drug Administration (FDA) eventually approved adalimumab as the only anti-TNF agent for use in adult NIU based on the findings of the VISUAL I, II, and subsequently, VISUAL III studies. Hiyama et al, in 2019, published a report of two cases of Behcet's uveitis treated successfully with adalimumab after it became refractory to steroids [ 13 ].…”
Section: Reviewmentioning
confidence: 99%
“…Though the efficacy of ADA in retinal vasculitis seemed inspiring, the primary disease of their patients was not solely confined to BU, and patients with spondylarthritis, Crohn’s disease and some unmentioned diseases were also included. In Asia, sporadic studies have reported similar outcomes, including Far Eastern areas such as Japan and Hong Kong ( Bawazeer et al, 2010 ; Al-Fakhri and Alsulaiman, 2019 ; Hiyama et al, 2019 ; Ho et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…The recommendation for the treatment of pediatric BD has been recently updated. In particular, the use of anti-TNFα drugs as a second-line option for refractory BD, and as a first-line treatment in severe ocular and neurological involvement, has demonstrated to be effective in improving the outcome of BD patients ( 10 , 18 ). In our case child developed cataracts due to long use of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%